Initiatives and Pitfalls in Medical Care and Education in a Digital Age (Bangladesh Journal of Medical Biochemistry, 2014)
DOI: http://dx.doi.org/10.3329/bjmb.v6i2.17641Bangladesh J Med Biochem 2013; 6(2): 37-39